2022
DOI: 10.3390/ijerph19031290
|View full text |Cite
|
Sign up to set email alerts
|

Feeling and Thinking about It Are Two Different Things: How to Capture Momentary Emotions of Extreme Sports in the Field

Abstract: To learn about extreme sports and what motivates such activities, we need to understand the emotions embedded in the experience itself. However, how we go about assessing these emotions might provide us with very different answers. An experience is a fleeting and ever-changing phenomenon, rich in detail and filled with nuances. What we remember and, therefore, what we are able to report from our experience might, however, be strikingly different to what we experienced. Our memories are grained by time, impaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 85 publications
0
0
1
Order By: Relevance
“…The inward negative emotions analysed (stress, beta = 0.910, p < 0.01; fear, beta = 0.862, p < 0.01; sadness, beta = 0.857, p < 0.01; frustration, beta = 0.853, p < 0.01; boredom, beta = 0.818, p < 0.01) were shown to be significant, stress being the most significant in the formation of hate towards extreme sports brands. This result contrasts with previous findings in the literature, which suggested that fear is the most important emotional underpinning of brand hate in a sporting context (Hetland, 2022; Hetland et al , 2018; Mirehie and Gibson, 2020). However, our results seem to be consistent with those of Tannenbaum et al (2015) and Dunn and Hoegg (2014), who argued that experienced extreme sports users may enjoy feeling fear and may even develop a greater attachment to a brand because it helps him/her take part in a challenging sport.…”
Section: Discussioncontrasting
confidence: 99%
“…The inward negative emotions analysed (stress, beta = 0.910, p < 0.01; fear, beta = 0.862, p < 0.01; sadness, beta = 0.857, p < 0.01; frustration, beta = 0.853, p < 0.01; boredom, beta = 0.818, p < 0.01) were shown to be significant, stress being the most significant in the formation of hate towards extreme sports brands. This result contrasts with previous findings in the literature, which suggested that fear is the most important emotional underpinning of brand hate in a sporting context (Hetland, 2022; Hetland et al , 2018; Mirehie and Gibson, 2020). However, our results seem to be consistent with those of Tannenbaum et al (2015) and Dunn and Hoegg (2014), who argued that experienced extreme sports users may enjoy feeling fear and may even develop a greater attachment to a brand because it helps him/her take part in a challenging sport.…”
Section: Discussioncontrasting
confidence: 99%